Digital-Based Differentiated Learning Management (A Case Study Of Elementary School Teachers In Kendari City) - Arifin, Sri Utami; Karsadi, Karsadi; Darnawati, Darnawati; Sukotjo, Endro (Journal of Neonatal Surgery, 2025)
The purpose of this study is to analyze and reveal in more depth the implementation of digital-based differentiated learning in elementary school education units in Kendari City, as well as the obstacles faced by teachers, and to provide solutions for the implementation of learning in the Merdeka Belajar Curriculum is carried out optimally. This was a descriptive study using a qualitative case study approach. Purposive sampling was used for informant determination. Data analysis techniques with data collection, data reduction, data presentation, and conclusions and verification. The results of the study show that the Merdeka Belajar program in elementary school education units in Kendari City has been implemented in stages. The implementation of digital-based differentiated learning is based on the principle that teachers create learning strategies by focusing on the categories of content/content, processes, products, and environments that are adjusted to the needs or conditions of students. The obstacles related to the curriculum often change, which causes confusion and hampers the education process. Efforts are made by teachers to carry out planning at the beginning so that the management of Differentiated Learning can run well and carry out professional development..